Miniature directive antennas. Issue 1 (13th February 2014) - Pigeon, M.; Delaveaud, C.; Rudant, L.; Belmkaddem, K.
Abstract : This paper presents the work carried out to assess the feasibility of miniature directive antennas. It is based on an analysis of the physical limits of antenna directivity in general and in particular as a function of their compact dimensions. A state of the art is done to identify and classify techniques to increase the directivity of compact antennas.